2011
DOI: 10.1093/toxsci/kfr204
|View full text |Cite
|
Sign up to set email alerts
|

Diglycolic Acid Is the Nephrotoxic Metabolite in Diethylene Glycol Poisoning Inducing Necrosis in Human Proximal Tubule Cells In Vitro

Abstract: Diethylene glycol (DEG), a solvent and chemical intermediate, can produce an acute toxic syndrome, the hallmark of which is acute renal failure due to cortical tubular degeneration and proximal tubular necrosis. DEG is metabolized to two primary metabolites, 2-hydroxyethoxyacetic acid (2-HEAA) and diglycolic acid (DGA), which are believed to be the proximate toxicants. The precise mechanism of toxicity has yet to be elucidated, so these studies were designed to determine which metabolite was responsible for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 37 publications
0
25
0
7
Order By: Relevance
“…The identification and characterization of DGA as a renal and hepatic toxicant has been unequivocally established using in vitro cellular, in vivo rat, and even human systems [3,[7][8][9][10]. A single case report of human exposure indicated that the heart could be negatively affected by DGA, but this effect has never been previously captured in vitro or in vivo animal models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification and characterization of DGA as a renal and hepatic toxicant has been unequivocally established using in vitro cellular, in vivo rat, and even human systems [3,[7][8][9][10]. A single case report of human exposure indicated that the heart could be negatively affected by DGA, but this effect has never been previously captured in vitro or in vivo animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been found that during the chemical synthesis of CMC, a byproduct called diglycolic acid (DGA) is also made and that DGA is a difficult impurity to eliminate [2,3]. DGA is a small four-carbon molecule consisting of two carboxylic acids connected together by an ether linkage (PubChem CID: 8088).…”
Section: Introductionmentioning
confidence: 99%
“…Like the toxic alcohols methanol and ethylene glycol, the metabolites of DEG (and not DEG itself) are responsible for the majority of its toxicity. As with other toxic alcohols, however, the parent compound causes altered mental status [14]. Like other toxic alcohols, DEG undergoes metabolism by both alcohol dehydrogenase and aldehyde dehydrogenase ( Figure 7) to form 2-hydroxyethoxyacetic acid (HEAA) [6,15] and diglycolic acid (DGA).…”
Section: Discussionmentioning
confidence: 99%
“…Like other toxic alcohols, DEG undergoes metabolism by both alcohol dehydrogenase and aldehyde dehydrogenase ( Figure 7) to form 2-hydroxyethoxyacetic acid (HEAA) [6,15] and diglycolic acid (DGA). While HEAA appears to be responsible for the acidosis in DEG poisoning, DGA is the metabolite responsible for kidney injury [14].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who survive initial toxicity may develop peripheral neuropathies, particularly of cranial nerve VII [21]. The exact cause of the metabolic acidosis and end-organ toxicity associated with DEG is unclear, but may be the result of accumulation of the DEG metabolites 2-hydroxyethoxyacetic acid and diglycolic acid [21][22][23]. Triethylene glycol (TEG) may also be found in brake fluid, though ingestions are rare.…”
Section: Case Continuedmentioning
confidence: 99%